(untitled) (Research, Society and Development, 2023)
Introduction: Physiotherapy has a lot to contribute to the care of cancer patients. In the case of gynecological tumors, which include the vulva, vagina, cervix, endometrium, uterine tube and ovary, in the face of the diagnosis of a life-threatening disease, an approach through palliative care is recommended, in order to prevent and alleviate symptoms. Objective: the present work aims to carry out a systematic review on the effectiveness of physiotherapy as an adjunctive treatment in patients with gynecological cancer. This is a systematic review of the literature. Methodology: The search for articles was carried out in the following online databases: Virtual Health Library (VHL), which includes SciELO (Scientific Electronic Library On Line), Lilacs (Latin American and Caribbean Literature in Health Sciences) and Pubmed databases. Results: The results showed that physiotherapeutic interventions for patients undergoing treatment for breast and gynecological cancer have varying levels of evidence to contribute to the prevention or attenuation of the physical-functional impairment symptoms caused by the treatments. Conclusion: It is concluded that, based on the existing research literature on the impact of physiotherapy on women with gynecological cancer, it is clear that the different approaches used are beneficial in improving the patient’s quality of life.